2013
DOI: 10.3109/03009742.2013.802009
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen cost of walking, physical activity, and sedentary behaviours in rheumatoid arthritis

Abstract: The oxygen cost of walking in this cohort of people with RA was similar to that of matched controls but there was an increase in time spent sedentary and a reduction in time spent at cadences commensurate with MVPA. Clinical symptoms such as depression, pain, and fatigue may explain the changes in activity/sedentary behaviours in people with RA and require further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 36 publications
3
18
0
1
Order By: Relevance
“…However, when controlled for potential explanatory variables, only reduced activity due to fatigue, physical fatigue and disease activity were found to be statistically significantly lower in patients being regularly physically active. Findings from this study support previous studies documenting low levels of physical activity and increased sitting time in patients with RA compared to controls [9,[28][29][30]. Although no direct comparison was made in the present study, we found that 27 % of the patients in our study reported being primarily sedentary compared to 16.4 % of the Danish general population [31].…”
Section: Discussionsupporting
confidence: 92%
“…However, when controlled for potential explanatory variables, only reduced activity due to fatigue, physical fatigue and disease activity were found to be statistically significantly lower in patients being regularly physically active. Findings from this study support previous studies documenting low levels of physical activity and increased sitting time in patients with RA compared to controls [9,[28][29][30]. Although no direct comparison was made in the present study, we found that 27 % of the patients in our study reported being primarily sedentary compared to 16.4 % of the Danish general population [31].…”
Section: Discussionsupporting
confidence: 92%
“…It is possible that some minutes are classified as 'no walking registered', by which the person was standing upright, or possibly making weight shifts and taking small steps that were unregistered by the SAM. It was shown previously by Paul et al [42] that these periods of incidental movement could account for up to four hours per day. Questionnaires such as the International PA questionnaires could be applied for this reason, however, have the drawback of potentially impaired recall to accurately quantify PA.…”
Section: Discussionmentioning
confidence: 82%
“…Joint disease in rheumatoid arthritis (RA) often limits participation in moderate and vigorous physical activities. Individuals with RA generally tend to be sedentary, as a result of polyarticular pain, stiffness, fatigue, and functional limitations (2)(3)(4). In a cross-sectional study of patients with RA from 21 countries, approximately 71% reported being sedentary and not engaging in regular physical activity (2).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with RA generally tend to be sedentary as a result of poly-articular pain, stiffness, fatigue, and functional limitations (24). In a cross-sectional study of patients with RA from 21 countries, around 71% reported being sedentary and not engaging in regular physical activity (2) While a physically active lifestyle in RA is important to decrease the risk of cardiovascular disease, (5) it might be unreasonable to expect that all individuals with RA can shift from their habitual sedentary behavior to regular participation in PA at moderate or higher intensity.…”
mentioning
confidence: 99%